2019
DOI: 10.1038/s41598-019-43855-7
|View full text |Cite
|
Sign up to set email alerts
|

Improving performance of 3D speckle tracking in arterial hypertension and paroxysmal atrial fibrillation by using novel strain parameters

Abstract: The function of left atrium (LA) is closely related to LA remodeling and one of the most important mechanisms is an increased deposition of fibrous tissue that often is the basis for LA electro-mechanical changes before the onset of atrial fibrillation (AF). This study evaluated LA shape and function, by investigating standard and novel strain parameters calculated by a new approach based on homologous times derived from 3D speckle tracking echocardiography (3DSTE) in hypertensive (HT) and paroxysmal atrial fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 42 publications
(44 reference statements)
0
17
0
Order By: Relevance
“…Fourth, this study investigated the utility of RV volume-derived variables only. Additional techniques, such as three-dimensional speckle tracking echocardiography, might be more suitable for the estimation of RV function [ 40 ]. Finally, because we could not perform an a priori power calculation, a relatively small sample size might have influenced the statistical power to detect the differences.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, this study investigated the utility of RV volume-derived variables only. Additional techniques, such as three-dimensional speckle tracking echocardiography, might be more suitable for the estimation of RV function [ 40 ]. Finally, because we could not perform an a priori power calculation, a relatively small sample size might have influenced the statistical power to detect the differences.…”
Section: Discussionmentioning
confidence: 99%
“…organ damage induced by AH and 3D-speckle tracking derived left atrial strains resulted early altered in hypertensive patients, even before left atrial dilation [62,63]. Higher cumulative SBP from early adulthood throughout middle age was associated with adverse left atrial remodelling, with higher left atrial volumes, increased reservoir, and impaired early diastolic strain rate indicating impaired conduit function.…”
Section: Advanced Imaging In Hypertensionmentioning
confidence: 97%
“…A study by Esposito et al explored LA function in 48 patients with hypertensive and paroxysmal AF, and showed that impairment of LA strain and strain rates were observed in both hypertensive and paroxysmal AF groups compared with control subjects. Three-dimensional strain provided more significant LA functional information and LA strain was an independent predictor of poor outcomes in patients with paroxysmal AF [ 90 ]. Table 3 illustrates current findings regarding assessment of LA function in HF patients using 3D-STE.…”
Section: Three-dimensional Speckle-tracking Echocardiography In Hf Pa...mentioning
confidence: 99%